Pengaruh Penerapan Strategi Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Fikih Kelas VII Di MTS Pembangunan Pulau Punjung - Tika Haironisa; Supriadi Supriadi; Fajriani Arsya; Ulfa Rahmi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research is motivated by the less varied learning strategies used by teachers. Because the teacher only uses the strategies used in learning that are not attractive to students. Caused by a lack of strategy in learning Jurisprudence by the teacher concerned. Most teachers use the lecture method in the learning process and cause students to feel less interested in the learning being carried out, as a result, student learning outcomes are unsatisfactory and score below the KKM. This research is a Quasi Experimental Design type Non equivalent control group design with a tendency of quantitative data the subject of this research is class VII Experimental class VII Control students at MTsS Pembangunan Pulau Punjung with a sample size of 60 students. The research sample is class VII Experiment with Cooperative Learning Strategy Teams Games Tournament Type, class VII Control using conventional methods. The data analysis technique uses the Normality Test with the Kolmogrov Smirnov formula, and the homogeneity test with Fisher's test followed by hypothesis testing with Independent t-test. Based on the results of the analysis and discussion of the research data from the results of the hypothesis test t test Tcount = 2.376 and Ttable = 2.012, then Tcount>Ttable so that H0 is rejected. So it can be concluded that there is an effect of using cooperative learning strategies of the team games tournament type on the learning outcomes of class VII fiqh at the Pulau Punjung Development MTs